STRATEGI PENGEMBANGAN USAHA TEMPE UMMI DI KELURAHAN WIJAYAPURA KECAMATAN JAMBI SELATAN KOTA JAMBI - Efni Anita; Refky Fielnanda; M Rizky (CV. KAMPUS AKADEMIK PUBLISING, 2023)
. This study aims to determine the strategy for developing the Tempe Ummi business at the Angso Duo Market, Jambi City and to determine the strengths, weaknesses, opportunities and threats to the Tempe Ummi business at the Angso Duo Market, Jambi City. The research method used is SWOT analysis. The results obtained from this study are the business development strategy applied to Tempe Ummi which includes 4P, namely in terms of products that have been processed using modern machines. In terms of price, Tempe Ummi sells its products at stable and cheaper prices than competitors. Meanwhile, in terms of location, Tempe Ummi's business location is strategic because it is in the Angso Duo Market, Jambi City, which makes the opportunity to develop a business very large. In terms of promotion, Tempe Ummi only promotes its products by word of mouth. Tempe Ummi is also developing a business from its sales system, there are supporting products that Tempe Ummi takes on the market from market agents. The strengths of Tempe Ummi are products that are processed using modern machines, affordable prices, strategic locations, supporting products, and prioritizing product quality to maintain consumer loyalty. Meanwhile, the weakness is that there is no special logo and there is no promotion using print media or social media. Opportunities from Tempe Ummi are increasing population, increasing market needs, product diversification, and technological developments for promotion. While the threats that exist and need to be considered by Tempe Ummi are the many competitors in the market and price competition.